Effectiveness of dolutegravir-based antiretroviral treatment for HIV-2 infection: retrospective observational study from Western India. (11th April 2020) - Pujari, Sanjay; Patel, Atul; Gaikwad, Sunil; Patel, Ketan; Dabhade, Digamber; Chitalikar, Abhishek; Joshi, Kedar; Bele, Vivek
Abstract: Background: Data on the use of dolutegravir for treatment of HIV-2 infection are limited. Objectives: To assess the effectiveness of dolutegravir in people living with HIV-2 (PLHIV-2). Methods: A retrospective chart review was performed in two clinics in Western India. PLHIV-2 initiated on dolutegravir-based regimens were included. Response to treatment in both treatment-naive (TN) and treatment-experienced (TE; substitution and not in the context of failure) was assessed by CD4 counts and HIV-2 viral load (VL) in a proportion of individuals. The primary objective was to assess immunological effectiveness (absence of a drop in absolute CD4 counts by more than 30% of baseline). Change in absolute CD4 counts was assessed by fitting a mixed-effects model. Results: Sixty-two PLHIV-2 treated with dolutegravir were included. The immunological effectiveness rates (95% CI) were 91.9% (82.4%–96.5%), 92% (81.1%–96.8%) and 91.6% (64.6%–98.5%) amongst all, TE and TN individuals, respectively. Median change in absolute CD4 counts at 6, 12 and 18 months were +29 cells/mm 3, +101 cells/mm 3 and +72 cells/mm 3, respectively. The virological effectiveness rates (HIV-2 VL <100 copies/mL) (95% CI) for all, TE and TN individuals were 88.8% (74.6%–95%), 89.6% (73.6%–96.4%) and 85.7% (48.6%–97.4%), respectively. Three clinical events were documented: spinal tuberculosis, relapsed non-Hodgkin's lymphoma and herpes simplex virus retinitis. One individual reported self-limiting somnolence. Conclusions: Dolutegravir was well tolerated and associated with immunological, virological and clinical effectiveness in both TN and TE PLHIV-2 in a large cohort from Western India. Dolutegravir-based ART is an excellent option for treatment of individuals with HIV-2 infection.